Smartphone-based remote monitoring of vision in macular disease enables early detection of worsening pathology and need for intravitreal therapy. Issue 1 (25th May 2021) - Islam, Meriam; Sansome, Stafford; Das, Radha; Lukic, Marko; Chong Teo, Kelvin Yi; Tan, Gavin; Balaskas, Konstantinos; Thomas, Peter B M; Bachmann, Lucas M; Schimel, Andrew M; Sim, Dawn A
Abstract : Background/aims: To assess the outcomes of home monitoring of distortion caused by macular diseases using a smartphone-based application (app), and to examine them with hospital-based assessments of visual acuity (VA), optical coherence tomography-derived central macular thickness (CMT) and the requirement of intravitreal injection therapy. Design: Observational study with retrospective analysis of data. Methods: Participants were trained in the correct use of the app (Alleye, Oculocare, Zurich, Switzerland) in person or by using video and telephone consultations. Automated threshold-based alerts were communicated based on a traffic light system. A 'threshold alarm' was defined as three consecutive 'red' scores, and turned into a 'persistent alarm' if present for greater than a 7-day period. Changes of VA and CMT, and the requirement for intravitreal therapy after an alarm were examined. Results: 245 patients performing a total of 11 592 tests (mean 46.9 tests per user) were included and 85 eyes (164 alarms) examined. Mean drop in VA from baseline was −4.23 letters (95% CI: −6.24 to −2.22; p<0.001) and mean increase in CMT was 29.5 µm (95% CI: −0.08 to 59.13; p=0.051). Sixty-six eyes (78.5%) producing alarms either had a drop in VA, increase in CMT or both and 60.0% received an injection. Eyes with persistent alarms had a greater loss of VA, −4.79 letters (95% CI: −6.73 to −2.85; p<0.001) or greater increase in CMT, +87.8 µm (95% CI: 5.2 to 170.4; p=0.038). Conclusion: Smartphone-based self-tests for macular disease may serve as reliable indicators for the worsening of pathology and the need for treatment.